Educational Chain Whisper Game for Improving Listening and Memory Based on Local Wisdom - Ahsanurrijal Ahsanurrijal; Fadly Akbar; Ahmad Ahmad; Ahmad Rizal Abdullah; Aswadi Ramli (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
This community service is focused on improving students' listening and memory skills through the implementation of an educational "chain whisper" game integrated with local wisdom. The background for this activity is the urgent need to strengthen students' listening and memory abilities amidst a lack of interactive learning methods that are relevant to the cultural context. It uses a participatory and educational approach in several stages: preparation, implementation, and evaluation. The main results show that this approach successfully generated student enthusiasm, encouraged active participation, and significantly improved their ability to listen for details and their memory for the information conveyed. In addition, this activity also helped foster students' appreciation for local cultural heritage and noble values. It is concluded that the chain whisper game rooted in local wisdom is an effective and enjoyable method for developing students' listening and memory skills while also preserving culture.